Effect of Spexin on Cell Viability in a Diabetic Neuropathy Model: An in vitro Study - Bahar, Mehmet Refik; Orhan, Seval Ulku; Ozcan, Mete; Tekin, Suat (Wiley, 2025)
[Abstract Not Available]
Keywords: Spexin; Diabetic Neuropathy; Dorsal Root Ganglia